Prevalence of Maxillo-Mandibular patterns in patients from 8.5 to 12 years old, using Ricketts Cephalometry in university orthopedic services - Cisneros, Danela (2020)
Objetive: To determine the prevalence of the different skeletal patterns in a sample of patients aged 8.5 to 12 years old, using Ricketts cephalometric analysis. Methods: A descriptive cross-sectional study was proposed, considering a sample consisting of 40 patients aged 8.5 to 12 years treated in the Orthopaedics Department at the University Clinic of The Universidad UTE, Quito-Ecuador, between July 2015 and February 2018. Ricketts summary analysis was used to determine the skeletal pattern and establish the maxilla-mandibular relationship; measurements of maxillary convexity, maxillary depth, facial axis and facial depth were recorded. The data collected was analysed using descriptive statistics, frequency analysis, measures of central tendency and dispersion. Results: The predominant skeletal pattern was Class II (52.5%), followed by the Class I skeletal pattern (40%) and Class III (7.5%) Conclusions: The most prevalent skeletal pattern was Class II. There was not a direct relationship or association with the patient's sex.